Point-defect engineering of nanoporous CuBi2O4 photocathode via rapid thermal processing for enhanced photoelectrochemical activity - Qu, Li; Tan, Runfa; Sivanantham, Arumugam; Kang, Min Je; Jeong, Yoo Jae; Seo, Dong Hyun; Kim, Sungkyu; Cho, In Sun (Journal of Energy Chemistry, 2022)
Engineering point defects such as metal and oxygen vacancies play a crucial role in manipulating the electrical, optical, and catalytic properties of oxide semiconductors for solar water splitting. Herein, we synthesized nanoporous CuBi2O4 (np-CBO) photocathodes and engineered their surface point defects via rapid thermal processing (RTP) in controlled atmospheres (O2, N2, and vacuum). We found that the O2-RTP treatment of np-CBO increased the charge carrier density effectively without hampering the nanoporous morphology, which was attributed to the formation of copper vacancies (VCu). Further analyses revealed that the amounts of oxygen vacancies (Vo) and Cu1+ were reduced simultaneously, and the relative electrochemical active surface area increased after the O2-RTP treatment. Notably, the point defects (VCu, Cu1+, and Vo) regulated np-CBO achieved a superb water-splitting photocurrent density of −1.81 mA cm−2 under simulated sunlight illumination, which is attributed to the enhanced charge transport and transfer properties resulting from the regulated surface point defects. Finally, the reversibility of the formation of the point defects was checked by sequential RTP treatments (O2-N2-O2-N2), demonstrating the strong dependence of photocurrent response on the RTP cycles. Conclusively, the surface point defect engineering via RTP treatment in a controlled atmosphere is a rapid and facile strategy to promote charge transport and transfer properties of photoelectrodes for efficient solar water-splitting.
Keywords: Catalytic properties; Charge transfer properties; Charge transport properties; Copper vacancy; Defect engineering; Electrical/optical properties; Nano-porous; Photoelectrochemicals; Rapid-thermal processing; Solar water splitting; Charge transport; Copper bismuth oxide; Copper vacancy; Nanoporous; Rapid thermal processing